THE UNIQUENESS OF THE CHRONOTOPOS IN THE NOVEL BY MAX KIDRUK “WHERE GOD IS NOT PRESENT” - Ogulchanska, O. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article deals with the uniqueness of the chronotopos in the novel by Max Kidruk “Where God is not present”. The research of leading scholars in various fields of science, such as M. Bakhtin, N. Kopistyanska, A. Temirbolat, O. Chicheryn, O. Ukhtomskyi and others, was dedicated to the problems of the time-spatial organization of the artistic text. The analyzed novel of the famous and popular modern Ukrainian writer has recently been published and has not yet been the subject of literary research. The main events in the work take place on the mountain summit in the array of Gasherbrum - Gasherbrum VI, where “Boeing 777” has crushed. Various time-space planes are harmoniously interwoven in the novel, due to the introduction of retrospections of different plans to the text. This contributes not only to the expansion of time-space coordinates, but also allows to use multidimensional analysis of the psychological portrait of the characters. While investigating the time and space of the novel, we rely on N. Kopistyanska's idea that space is not only a place and a background of action; it is the vector that influences the formation of the character, moral properties of the individual. During the analysis of the chronotopos of the novel “Where God is not present”, attention is focused on the character-building function of one's or another's space, which is one of the important means of psychologization. The psychological space of characters and their relationship with the outside is analyzed. The titles of the sections of the novel “Where God is not present” point to spatial boundaries, where chronological events will take place: “Airport”, “Airplane”, “Mountain”. The chronotopos of each section is expanded by the introduction of retrospectives. The writer uses various forms of time specification, such as: the exact definition of cyclic coordinates (indication of seasons, time of day, hours, minutes) and indication of the years in which events occur. In the novel, various countries, cities (Beijing, the Netherlands, Dubai, Sweden, Zaporizhzhia, Kyiv, Moscow, etc.) are mentioned spontaneously.